Analisis Kinerja Keuangan PT Tembaga Mulia Semanan Tbk. Periode 2019-2022 - Mukhlisiah, Rizka; Syach Ginting, M. Enteguh (FKIP, Universitas Banten Jaya, 2024)
One of the main indicators related to the business continuity (going concern) of a company is the company's financial performance. The trust of interested parties such as shareholders, managers and creditors will increase if the company's financial performance is of good quality. This research aims to assess the financial performance of PT Tembaga Mulia Semanan Tbk. 2019-2022, namely calculating liquidity ratios (current ratio and quick ratio), solvency ratios (debt to asset ratio and debt to equity ratio), profitability ratios (return on investment and return on equity), and activity ratios (inventory turnover and fixed asset turnover) for the 2019-2022 period. This research applies a descriptive quantitative analysis method using secondary data, namely audited financial reports in the form of profit and loss statements and financial position reports as well as books related to financial report analysis. Financial reports are taken from published data from the Indonesian Stock Exchange and PT Tembaga Mulia Semanan Tbk. The results of the research are PT Tembaga Mulia Semanan Tbk. describes poor financial performance in 2019-2022 which is characterized by the current ratio and quick ratio, debt to asset ratio and debt to equity ratio, ROI and ROE, which are below industry standards as well as fixed asset turnover and inventory turnover with values ​​above industry standards.